2008
DOI: 10.1007/s10661-008-0626-6
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric inorganic nitrogen deposition to a typical red soil forestland in southeastern China

Abstract: A 2-year monitoring study was conducted to estimate nitrogen deposition to a typical red soil forestland in southeastern China. The dry deposition velocities (V(d)) were estimated using big leaf resistance analogy model. Atmospheric nitrogen dry deposition was estimated by combing V(d) and nitrogen compounds concentrations, and the wet deposition was calculated via rainfall and nitrogen concentrations in rainwater. The total inorganic nitrogen deposition was 83.7 kg ha(-1) a(-1) in 2004 and 81.3 kg ha(-1) a(-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 53 publications
(59 reference statements)
0
12
0
1
Order By: Relevance
“…also be significant since the process occurs all the time. For example, earlier studies suggested that N dry deposition contributed 16Á79% to the total wet'dry deposition at various locations in China (Fan et al, 2009;Chen et al, 2011;Pan et al, 2012;Shen et al, 2013), 25Á58% in the United States (Munger et al, 1998;Sparks et al, 2008;Beem et al, 2010) and 10Á50% in Canada .…”
Section: Introductionmentioning
confidence: 99%
“…also be significant since the process occurs all the time. For example, earlier studies suggested that N dry deposition contributed 16Á79% to the total wet'dry deposition at various locations in China (Fan et al, 2009;Chen et al, 2011;Pan et al, 2012;Shen et al, 2013), 25Á58% in the United States (Munger et al, 1998;Sparks et al, 2008;Beem et al, 2010) and 10Á50% in Canada .…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that in rainwater the main anions SO 2− 4 and NO − 3 are acidic, while the dominant cations NH + 4 and Ca 2+ are important in neutralizing the acidity of precipitation. In recent years, the acidic precipitation in southeastern China has become more serious (Shen and Liu 2009;Fan et al 2009). Hangzhou, one of the most important cities in this region, which has huge population and highly developed economy and a famous tourism city, suffered serious acid rain in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Human impact on atmospheric depositions is high (Pye et al 2009; Fan et al 2009; Aas et al 2007) and particularly depositions of nitrogen (N), sulphur (S), phosphorus (P) and potassium (K) have considerable influence on ecosystems (Cinderby et al 1998; Adams 2003; Rockström et al 2009). N and P cycles are among the most heavily influenced earth system processes by human (Rockström et al 2009; Phoenix et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Even for remote tropical areas, a substantial increase of N deposition is assumed and its potential impacts are being investigated (Corre et al 2007; Phoenix et al 2006). A growing number of studies in the northern hemisphere (Bytnerowicz et al 2002; Fenn et al 2000; Fenn and Poth 2004; Gassmann 2004) have shown increasing atmospheric depositions related to human activities and associated environmental impacts (Fan et al 2009; Aas et al 2007; Curtis et al 2009; Phoenix et al 2006). For example, an excess of N leads to a multitude of undesirable reactions of the affected ecosystems, which can be: (a) acidification (Adams 2003), (b) contamination of ground and surface water (Curtis et al 2009) and (c) increasing greenhouse gas emissions, for example N 2 O (Veldkamp et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation